1999
DOI: 10.1183/09031936.99.13364799
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum in adolescents with severe stable asthma. Safety and the relationship of cell counts and eosinophil cationic protein to clinical severity

Abstract: This study examined the safety of sputum induction and the relation between sputum cell counts and clinical parameters in adolescents with severe persistent asthma.Within 5 days, induced sputum and reversibility in forced expiratory volume in one second (FEV1), quality of life, provocative concentration causing a 20% fall in FEV1 (PC20) of adenosine monophosphate and histamine, exercise-induced bronchoconstriction, overall asthma severity index, and blood eosinophils were collected in 20 atopic adolescents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 30 publications
3
54
0
1
Order By: Relevance
“…Despite the pre-treatment with 200 µg salbutamol, some of the patients developed an excessive drop of lung function parameters. This is in agreement with all the previous observations of pre-treatment not giving a complete protection against bronchospasm (7,11,15,16). Some authors have found that administration of nebulised salbutamol during the sputum induction could improve bronchoprotection in asthma patients (22).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Despite the pre-treatment with 200 µg salbutamol, some of the patients developed an excessive drop of lung function parameters. This is in agreement with all the previous observations of pre-treatment not giving a complete protection against bronchospasm (7,11,15,16). Some authors have found that administration of nebulised salbutamol during the sputum induction could improve bronchoprotection in asthma patients (22).…”
Section: Discussionsupporting
confidence: 81%
“…This naturally resulted in longer inhalation times and higher concentrations inhaled. The proportion of inductions ending after the final, 5% saline, concentration was 50% in our study compared to 0%, 4% and 16% in other studies (11,17,22). Despite the pre-treatment with 200 µg salbutamol, some of the patients developed an excessive drop of lung function parameters.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Although the drop in postsalbutamol forced expiratory volume in one second (FEV1) after inhalation was larger in asthmatics than in normals a fall exceeding 20% only occurred in 3/37 patients. Sputum induction using hypertonic saline is also efficacious and safe in adolescent asthmatics [13,14] and isotonic saline sputum induction appears to be safe in children with acute asthma [15]. Although the feasibility of sputum induction has been reported in patients with CF [16], a systematic study of sputum induction in young CF patients is lacking.…”
mentioning
confidence: 99%
“…Safety and practicality are the most obvious. The method of obtaining induced sputum is relatively noninvasive and can be carried out at random [2] and repeatedly in subjects with varying disease severity [3][4][5][6][7][8][9][10][11][12][13]. Therefore, it is not surprising that the examination of induced sputum has become the most clinically applicable method for the assessment of airway inflammation.…”
mentioning
confidence: 99%